2013
DOI: 10.3390/ijerph10105146
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Cytotoxic Potential of Cigarette Smoke and Electronic Cigarette Vapour Extract on Cultured Myocardial Cells

Abstract: Background: Electronic cigarettes (ECs) have been marketed as an alternative-to-smoking habit. Besides chemical studies of the content of EC liquids or vapour, little research has been conducted on their in vitro effects. Smoking is an important risk factor for cardiovascular disease and cigarette smoke (CS) has well-established cytotoxic effects on myocardial cells. The purpose of this study was to evaluate the cytotoxic potential of the vapour of 20 EC liquid samples and a “base” liquid sample (50% glycerol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
146
3
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(167 citation statements)
references
References 41 publications
9
146
3
7
Order By: Relevance
“…In fact, the Flavors and Extracts Manufacturers' Association (FEMA) has issued an official statement mentioning that flavor ingredients are evaluated for exposure through ingestion only; thus, any results cannot be extrapolated to use through inhalation. 5 Studies have shown that any cytotoxic properties of e-cigarette liquids and aerosol, although significantly lower than tobacco smoke, may be attributed to specific flavors, [6][7][8] indicating that further research is certainly needed in this area.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the Flavors and Extracts Manufacturers' Association (FEMA) has issued an official statement mentioning that flavor ingredients are evaluated for exposure through ingestion only; thus, any results cannot be extrapolated to use through inhalation. 5 Studies have shown that any cytotoxic properties of e-cigarette liquids and aerosol, although significantly lower than tobacco smoke, may be attributed to specific flavors, [6][7][8] indicating that further research is certainly needed in this area.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there is an increasing number of publications concerning the influence of electronic cigarettes on the human body, as well as literature comparing traditional and electronic smoking. What is more, Farsalinos et al 17 showed that cinnamon-flavored liquids have a cytotoxic influence on myoblasts isolated from rats' hearts. Furthermore, Yu et al 18 presented findings of changes in the DNA which resulted from e-cigarette aerosol, which were similar to those caused by tobacco smoke.…”
Section: Discussionmentioning
confidence: 99%
“…Sağlıklı sigara içici-lerinde e-sigara kullanımını takiben beş dakika içinde havayolu rezistansının, empedansın ve oksidatifstresin arttığı gösterilmiştir (24) . Ratların kardiyak myoblast hücre kültüründe beş farklı e-sigara üreticisinin 20 refill solüsyonundaki çeşitli tatlandırıcıların sitotoksik olduğu (25) ; klinik deneylerde ise e-sigaraların sistolik ve diyastolik kan basıncını yükselttiği kalp hızını artırdığı (26) gösterilmiştir.…”
Section: Akut Fizyolojik Etkileriunclassified